V.10 - Mishra, Madhu S. (ed.) (Calcutta, 1991)
Development of rural sector plays a crucial role in the context of India's longterm economic development and growth objectives. The need for appropriate strategies for accelerating the pace of rural development activities in increasingly felt by planners, development administrators, researchers and the organisations involved. in implementation of such activities. It is often realised that the existing information as well as knowledge base on the rural sector are inadequate for ensuring effectiveness in the above endeavour. In view of he diversities and complexities involved in understanding the operation of different systems and sub-systems in the rural sector, the available literature on the subject seem to be meagre and are widely scattered often lacking in time series date. This proves extremely inadequate for proper understanding of the rural sectors and analysis of the emerging issues in solving problems of developmental efforts. From the perspective of the greater emphasis being given to the integrated rural development programme by the government and other organisations in the recent years, the effective planning and implementation, there is scope for enhancing our knowledge, information and data base on the rural sector through systematic research and studies in the areas of rural economy, ecology and society. Despite our experience of rural development programmes through our planning efforts, to-day the need for up to-dating our knowledge and understanding of the rural sector thus seems to be greater than even before for ensuring the desired goals of developing rural India. Under the Rural Development in Management Programme of the Institute we have been mainly interested in examining the sources and applicability of management concepts and systems to the rural sector with a view to acquiring greater understanding of the complexities in developments of rural sector. During the last ten years we have concentrated on (a) compilation of information relating to rural sector (with main emphasis on eastern region) and creation of data bases on development indicators, socio-economic activities and rural organisations; (b) inter-disciplinary research and consultancy projects in the related fields, rural industrialisation and employment, rural markets and distribution system, development administration and institutions, agrarian structure and organisation and appropriate technology etc.: (c) organisation of seminars, workshop, discussion groups for regular interaction and exchange of views among academic institution, developmental agencies, industrial house, financial institutions, government and voluntary organisations to evolve new areas of research and strategies for rural development; (d) organisation of training and teaching programmes; and (e) publication of information collected from primary and secondary sources on the related areas. It is proposed to phase out the different activities under this programme with emphasis on data gathering, identification of basic knowledge areas, evaluation of existing knowledge for developing specification and utilisation of outputs as inputs for further diversifications. In is hoped that this would not only help in undertaking systematic analysis of the complexities involved in rural development and related activities but also in providing appropriate management for improving the effectiveness of various programmes and strategies.
Keywords: Bibliography management rural development